1993
DOI: 10.1038/362068a0
|View full text |Cite
|
Sign up to set email alerts
|

Selection for T-cell receptor Vβ–Dβ–Jβ gene rearrangements with specificity for a myelin basic protein peptide in brain lesions of multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system in which a restricted cellular immune response has been observed. In order to establish whether such T cell responses are likely to be antigen-specific particularly with regard to myelin basic protein (MBP), we analysed T-cell receptor (TCR) gene rearrangements directly from MS brain plaques, using the polymerase chain reaction on reverse transcribed messenger RNA, and compared these with TCR of previously described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
209
6
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 402 publications
(234 citation statements)
references
References 16 publications
16
209
6
3
Order By: Relevance
“…Although skewing of the TCRBV repertoire and sharing of common amino acid motifs in the CDR3 region have been reported in other HLA class II D region-associated diseases (e.g. rheumatoid arthritis, multiple sclerosis) [39,40], our analysis revealed no skewing of the TCRBV repertoire in coeliac disease patients in the early period after gluten challenge. Our analysis would not, however, detect minor changes that might occur in the representation of antigenspecific clones within V families.…”
Section: Discussioncontrasting
confidence: 79%
“…Although skewing of the TCRBV repertoire and sharing of common amino acid motifs in the CDR3 region have been reported in other HLA class II D region-associated diseases (e.g. rheumatoid arthritis, multiple sclerosis) [39,40], our analysis revealed no skewing of the TCRBV repertoire in coeliac disease patients in the early period after gluten challenge. Our analysis would not, however, detect minor changes that might occur in the representation of antigenspecific clones within V families.…”
Section: Discussioncontrasting
confidence: 79%
“…Immunoscope analysis was performed with a modified protocol. 27,35 A measure of 2 ml of BV14-BC or BV16-BC PCR products were used as templates and run-off reactions were performed with a single internal fluorescent label for each of the 6FAM (expand)-labeled BC or BJ primers ( Table 5). The reaction profile consisted of 30 s at 941C denaturation temperature and 15 cycles at 941C for 45 s; at 551C for 45 s, at 721C for 1 min, followed by 721C for 5 min as an extension step.…”
Section: Immunoscope Analysismentioning
confidence: 99%
“…With an outstanding postdoc Jorge Oksenberg, now a professor at UCSF, and with a renowned collaborator Claude Bernard from Australia, we also showed that, even in lesions in MS brain, there was evidence of restricted T-cell receptor expression (54,55). Tomas Olsson and colleagues took these results forward into the clinic, targeting T cells with VB5.2 T-cell receptors.…”
Section: Early Years On the Stanford Facultymentioning
confidence: 87%